MEDIASI PENAL DITINGKAT KEPOLISIAN DALAM MEWUJUDKAN RESTORATIF JUSTICE - NI Made Rai Sukardi; I Wayan Eka Artajaya (Jurnal Ilmiah Raad Kertha, 2022)
This research is entitled, "Penal Mediation at Police Level in Realizing Restorative Justice." The problem discussed in this study is the application of mediation by the police in handling criminal acts as an effort to realize restorative justice and factors that impede the application of mediation by the police in realizing restorative efforts. Justice. The writing method used in this study is Normative research. Mediation by the police in handling criminal cases as an effort to realize restorative justice. Criminal case resolution is specifically the crime of the police. The process of mediation is carried out by police investigators in order to resolve legal problems that occur, so that both parties feel they want justice. The inhibiting factor for implementing a restorative justice in the settlement of criminal cases is: The absence of legal rules governing the process of mediation in settlement criminal cases, the discretionary authority possessed by the police in taking steps to settle criminal cases has a digression, law enforcers sometimes hold fast to the formal legalistic principle so that the police, namely investigators, override the sense of justice and benefit in society